Odd and total harmonic insulator distortion of leakage current as a tool to estimate contamination level - Salem, Ali Ahmed; Abd-Rahman, Rahisham; Saufi, Muhammad; Abdul Hamid, Haziah; Hussin, Nuriziani (Penerbit UTHM, 2020)
Insulator contamination monitoring of distribution and transmission systems is inspiring many researchers in power system field [1]-[7]. The online leakage current (LC) wireless monitoring system provided insulators status diagnosis during service and send an alarm on pre-flashover occurrence [4]. In relation to pollution severity studies, recent researches have shown that odd harmonics of LC is suitable to produce the best results in predicting the contamination severity rate [3].